A new day - Meltzer, Brad; Santat, Dan (New York : Dial Books for Young Readers, 2021)
"After Sunday quits being a day of the week, the other days of the week try out all sorts of candidates, until an act of kindness reminds them all that a little appreciation can go a long way"--
Ages 3-5.
Grades K-1.
Keywords: Kindness -- Juvenile fiction; Days -- Juvenile fiction; Humorous stories; Picture books